Laser‐Induced Transient Anisotropy and Large Amplitude Magnetization Dynamics in a Gd/FeCo Multilayer. Issue 36 (25th October 2022) - Blank, Thomas G.H.; Hermanussen, Sten; Lichtenberg, Tom; Rasing, Theo; Kirilyuk, Andrei; Koopmans, Bert; Kimel, Alexey V.
Abstract: Ultrafast laser‐induced dynamics in a ferrimagnetic gadolinium iron cobalt (Gd/FeCo) multilayer with a magnetization compensation temperature of T M  = 320 K is studied at room temperature as a function of laser‐fluence and strength of the applied magnetic field. The dynamics is found to be substantially different from that in archetypical GdFeCo alloys, and depending on the laser fluence one can distinguish two different regimes. At low laser fluence (⩽1.6 mJ cm ‐2 ), ultrafast laser excitation of the medium triggers spin precession of an extraordinary large amplitude reaching over 30°. At high laser fluence (⩾2.2 mJ cm ‐2 ), the pump heats the medium over the magnetization compensation point, spin precession reduces significantly in amplitude and the process of field‐assisted reversal of magnetization of Gd and FeCo is launched. It is argued that such a distinctly different laser‐induced magnetization dynamics in the multilayers compared to the alloys is due to the symmetry breaking at the numerous interfaces, giving rise to additional surface anisotropy. The temperature dependence of the latter is found to be the key ingredient in the mechanism of ultrafast laser‐induced magnetization dynamics in ferrimagnetic multilayers. Controlling the amount and properties of interfaces in multilayers can thus serve as a mean to achieve efficient ultrafast all‐optical control of magnetism. Abstract : The ultrafast magnetization dynamics in a ferrimagnetic Gd/FeCo multilayer is found to be substantially different from that observed in GdFeCo alloys. The effects can be understood by considering thermal transient changes of the magnetic anisotropy field. In this respect, the symmetry‐breaking interfaces distinguish the multilayer from the alloy, giving rise to additional and controllable contributions to the anisotropy.